A gestational profile of placental exosomes in maternal plasma and their effects on endothelial cell migration. - Carlos Salomon (Public Library of Science (PLoS), 2014)
Studies completed to date provide persuasive evidence that placental cell-derived exosomes play a significant role in intercellular communication pathways that potentially contribute to placentation and development of materno-fetal vascular circulation. The aim of this study was to establish the gestational-age release profile and bioactivity of placental cell-derived exosome in maternal plasma. Plasma samples (n = 20 per pregnant group) were obtained from non-pregnant and pregnant women in the first (FT, 6-12 weeks), second (ST, 22-24 weeks) and third (TT, 32-38 weeks) trimester. The number of exosomes and placental exosome contribution were determined by quantifying immunoreactive exosomal CD63 and placenta-specific marker (PLAP), respectively. The effect of exosomes isolated from FT, ST and TT on endothelial cell migration were established using a real-time, live-cell imaging system (Incucyte). Exosome plasma concentration was more than 50-fold greater in pregnant women than in non-pregnant women (p<0.001). During normal healthy pregnancy, the number of exosomes present in maternal plasma increased significantly with gestational age by more that two-fold (p<0.001). Exosomes isolated from FT, ST and TT increased endothelial cell migration by 1.9±0.1, 1.6±0.2 and 1.3±0.1-fold, respectively compared to the control. Pregnancy is associated with a dramatic increase in the number of exosomes present in plasma and maternal plasma exosomes are bioactive. While the role of placental cell-derived exosome in regulating maternal and/or fetal vascular responses remains to be elucidated, changes in exosome profile may be of clinical utility in the diagnosis of placental dysfunction.